2023
DOI: 10.1101/2023.02.24.529709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sub-second fluctuations in extracellular dopamine encode reward and punishment prediction errors in humans

Abstract: In the mammalian brain, midbrain dopamine neuron activity is hypothesized to encode reward prediction errors that promote learning and guide behavior by causing rapid changes in dopamine levels in target brain regions. This hypothesis (and alternatives regarding dopamine's role in punishment-learning) has limited direct evidence in humans. We report intracranial, subsecond measurements of dopamine release in human striatum measured while volunteers (i.e., patients undergoing deep brain stimulation (DBS) surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…According to the canonical view, the mesocorticolimbic system is responsible for signaling both the reward value and associated expectations. However, recent evidence 19,58 and our human fMRI 59,60 and rodent studies 61,62 implicate this circuit in aversive states and chronic pain. Yet, aversion-related mesocorticolimbic adaptations with long-term opioid exposure remain unknown 29 .…”
Section: Discussionmentioning
confidence: 77%
“…According to the canonical view, the mesocorticolimbic system is responsible for signaling both the reward value and associated expectations. However, recent evidence 19,58 and our human fMRI 59,60 and rodent studies 61,62 implicate this circuit in aversive states and chronic pain. Yet, aversion-related mesocorticolimbic adaptations with long-term opioid exposure remain unknown 29 .…”
Section: Discussionmentioning
confidence: 77%
“…FSCV is a method for measuring the fluctuations of dopamine, serotonin, and norepinephrine concentrations in human brain tissue [21][22][23][24][25][26][27] . For the current report, FSCV recordings were made during 15 DBS surgeries while study participants (N = 9) played 60 rounds of the ultimatum game 28,29 approximately 10 minutes after a PFC biopsy was obtained.…”
Section: Identification Of Fscv De Signaturesmentioning
confidence: 99%
“…This knowledge gap of how DA neurons integrate information about reward expectation and reward into RPEs is particularly salient in the human literature, due to difficulties of recording activity from deep DA nuclei in living humans. Previous studies have leveraged neurosurgical interventions to examine human dopaminergic activity using microelectrode recordings to record single unit activity from the SN 6,7 , or voltammetry approaches to record dopamine transients in the striatum [19][20][21] . These studies have demonstrated that post-reward activity in the human dopaminergic system reflects reward signals, including unexpected rewards and RPEs.…”
Section: Introductionmentioning
confidence: 99%